KOKAND AND ANDIJAN ARCHITECTURE: MADRASAS AND PALACES OF THE 19TH CENTURY - A. R. Abobakirov (Modern American Journals, 2025)
The architecture of Kokand and Andijan in the 19th century represents a crucial chapter in the development of Uzbek cultural and artistic heritage, reflecting both the continuity of Islamic and Central Asian traditions and the transformations brought about by political, social, and imperial contexts. As the Fergana Valley became a vibrant center of intellectual, spiritual, and political life, Kokand emerged as the capital of the Kokand Khanate, producing monumental architectural ensembles such as the Khudayar Khan Palace and numerous madrasas, while Andijan, a historically significant city, contributed with mosques, madrasas, and civic complexes that combined functionality with ornamentation. This study explores the architectural forms of these two cities in the 19th century, with a special focus on the madrasas and palaces that symbolized both religious devotion and political authority. Using historical-architectural methodology, the paper examines archival records, architectural surveys, and stylistic comparisons to contextualize these monuments within broader regional and imperial frameworks. Results indicate that Kokand and Andijan architecture of the period successfully synthesized Islamic ornamental vocabulary, Turkic spatial traditions, and, increasingly, Russian imperial influences, producing structures that remain significant as cultural heritage sites. The discussion emphasizes the dual role of these monuments as both religious and political symbols, while the conclusion stresses their enduring contribution to Uzbekistan’s architectural identity and their importance for contemporary heritage preservation.
Keywords: Kokand Architecture; Andijan Architecture; Khudayar Khan Palace; 19th Century Madrasas; Fergana Valley; Uzbek Cultural Heritage